Revision of Palaearctic and Oriental Necrophila Kirby & Spence, part 1: subgenus Deutosilpha Portevin (Coleoptera: Silphidae) - Růžička, Jan; Schneider, Jan (Zootaxa, 2011)
Taxonomic revision of the subgenus Deutosilpha Portevin, 1920 (of Necrophila Kirby & Spence, 1828) through southeastern Asia is presented. Two species are recognised: (1) N. (D.) rufithorax (Wiedemann, 1823), comb. nov. (ex Deutosilpha), with Oiceoptoma tetraspilotum Hope, 1833 as confirmed junior subjective synonym, from India, Nepal and Sri Lanka; and (2) N. (D.) luciae Růžička & Schneider, sp. nov. from Thailand, Laos, Vietnam and China: Sichuan province. A lectotype is designated for Silpha rufithorax Wiedemann, 1823 and Oiceoptoma tetraspilotum Hope, 1833. Morphology-based diagnosis and key to adults of both species are produced. Georeferenced records for both species are mapped.